2004
DOI: 10.1210/jc.2003-032189
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone Activates Nitric Oxide Synthesis in Human Endothelial Cells

Abstract: After the unexpected findings of the Women's Health Initiative trial, indicating that traditional cardiovascular risk markers fail to predict the effects of hormone replacement therapy, it is of interest to characterize how steroids act on vascular cells. This is particularly important for tissue-specific drugs such as tibolone, whose actions may differ from other preparations. Because nitric oxide (NO) is a key regulator of vascular tone and atherogenesis, we studied its regulation by tibolone and its metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
0
16
0
3
Order By: Relevance
“…In a previous study (Vos et al, 2002) with radiolabeled tibolone, 17␤-mono-S metabolites constituted less than 10% of the radiolabel administered. Based on these results, the limited sample volumes, and because 17-mono-S compounds cannot readily be desulfated (Goldzieher et al, 1988;de Gooyer et al, 2001;Takanashi et al, 2003;Simoncini et al, 2004) to receptor-binding metabolites, it was decided to develop validated assays for the di-S metabolites and only for 3-mono-S metabolites. The results obtained with the semiquantitative analysis proved to be similar to those obtained with the validated assays.…”
Section: Pk Of Tibolone (Metabolites) In Monkey Plasma and Excretamentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Vos et al, 2002) with radiolabeled tibolone, 17␤-mono-S metabolites constituted less than 10% of the radiolabel administered. Based on these results, the limited sample volumes, and because 17-mono-S compounds cannot readily be desulfated (Goldzieher et al, 1988;de Gooyer et al, 2001;Takanashi et al, 2003;Simoncini et al, 2004) to receptor-binding metabolites, it was decided to develop validated assays for the di-S metabolites and only for 3-mono-S metabolites. The results obtained with the semiquantitative analysis proved to be similar to those obtained with the validated assays.…”
Section: Pk Of Tibolone (Metabolites) In Monkey Plasma and Excretamentioning
confidence: 99%
“…In a PK analysis (Vos et al, 2002) using radiolabeled tibolone, qualitative metabolite patterns have been determined with high-performance liquid chromatography in plasma, urine, and feces from three healthy, postmenopausal subjects, indicating that more than 75% of the metabolites in the circulation are monosulfated (mono-S) or disulfated (di-S) and that more than 80% of the radiolabel is excreted after 192 h, predominantly in the feces. Whereas sulfation renders compounds inactive at receptors, the enzyme sulfatase may readily reconvert 3-mono-S but not 17-mono-S metabolites into active receptor binding metabolites (Goldzieher et al, 1988;de Gooyer et al, 2001;Takanashi et al, 2003;Simoncini et al, 2004). As in postmenopausal women, pharmacological studies with tibolone in monkeys have shown that tibolone reduces hot flushes (Jelinek et al, 1984) and that 0.2 mg/kg/day tibolone for 2 years protects ovariectomized cynomolgus monkeys against bone loss, without stimulation of breast and endometrium (Clarkson et al, , 2004Cline et al, 2002;Williams et al, 2002).…”
mentioning
confidence: 99%
“…Sulfation at the 17-position seems to be irreversible (de Gooyer et al, 2001) as shown in rats with double-labeled estradiol sulfate (Takanashi et al, 2003). Two studies suggest, however, that 17-sulfation may, to some degree, be reversible (Goldzieher et al, 1988;Simoncini et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…All the analytes were determined by liquid chromatography followed by tandem mass spectrometry procedures (Xendo, Groningen, The Netherlands). It was decided to develop assays for the 3-mono-S metabolites only because 1) the supply of most tissues was very limited; 2) the levels of the 17␤-mono-S metabolites were shown in a pilot experiment to be very low in myometrium and liver; and 3) the 17␤-mono-S metabolites cannot readily be reconverted to the nonsulfated metabolites again (Goldzieher et al, 1988;de Gooyer et al, 2001;Takanashi et al, 2003;Simoncini et al, 2004). In a previous study (Vos et al, 2002) with radiolabeled tibolone, 17␤-mono-S metabolites constituted less than 10% of the radiolabel administered.…”
Section: Methodsmentioning
confidence: 99%
“…Tibolone binds and activates the estrogen receptor by means of its 3-hydroxy-metabolites (Kloosterboer 2001). The progestogenic/androgenic metabolite, the -4 isomer, had a neutral effect on NO synthesis, which implies that the effect of tibolone on NO production in endothelial cells is likely to be mediated by estrogen receptors (Simoncini et al 2004).…”
Section: R Campisi and F D Marengomentioning
confidence: 99%